Development of PNA electrochemical biosensor based on screen-printed electrode-modified amine-functionalized graphene composite for Mycobacterium tuberculosis detection - Mat Zaid, Mohd Hazani (2017)
Agarose gel electrophoresis is a fundamental and essential technique for analysis of PCR products related of mycobacterium tuberculosis. However this technique imposes some sort of limitation such as unquantifiable results and low specificity. Therefore, a novel PNA electrochemical biosensor based on modified screen printed carbon electrode (SPCE) has been developed for detection of mycobacterium tuberculosis which could overcome the limitation of agarose gel electrophoresis technique. In this study, the fabricated electrochemical biosensor SPCE has been modified with two different nanomaterial consist of amine functionalized reduced graphene oxide (NH2-GO) composited with water soluble CdS Quantum dots (QDs) and NH2-GO composited with Tempo-nanocellulose (TNCC) for enhance sensitivity detection of target ssDNA sequence related to Mycobacterium tuberculosis. The prepared composite materials have been characterized by Raman, FTIR, and TEM. Meanwhile, field emission microscope (FE-SEM) and energy dispersive X-ray spectroscopy (EDX) analysis had confirmed that both nanomaterials (NH2-GO/QDs and NH2-GO/TNCC) were deposited and uniformly distributed on the surface of SPCE. Furthermore, based on impedance spectroscopy (EIS) and cyclic voltammetry characterization (CV), the modified electrode has shown an enhancement of surface active area and better conductivity compared to the unmodified electrode. Subsequently, both fabricated electrode was further explored as electrochemical biosensor platform based on immobilized PNA probe and methylene blue (MB) was used as an electrochemical indicator to evaluate the performance of PNA electrochemical biosensor. At optimum condition, PBS buffer was choose as supporting buffer, PNA probe concentration of 10 μM, ratio of EDC/NHS of 4 mM:5 mM, MB immersion time of 45 min, MB concentration of 35 μM, pH MB of 7.5, and hybridization temperatures of 27 ᴼC for NH2-GO/QDs/SPCE biosensor. Meanwhile, for biosensor based on NH2-GO/TNCC/SPCE, The optimum detection can be reach by using borate saline buffer as supporting buffer, PNA probe concentration of 20 μM, ratio of EDC/NHS concentration of 6 mM:5 mM (v/v), MB immersion time of 30 min, MB concentration of 45 μM, pH MB of 9 and hybridization temperature at 40 ᴼC . Moreover, reproducibility study exhibited good result with the RSD value of 4.46% for SPCE/NH2-GO/QDs and 5.96% for SPCE/NH2-GO/NCC, respectively with sufficient selectivity to discriminate between complementary, non-complimentary and one base mismatch DNA. The reduction peak current of MB after hybridization was proportional to the concentration of target MTB DNA in the range from 1.0×10−13 to 1.0×10−6 mol/L with a detection limit of 8.948 ×10−13 M for NH2-GO/QDs/SPCE and 3.14 x 10-14 M for NH2-GO/TNCC/SPCE, respectively. In addition, the stability study has also shown that both fabricated biosensor could be stored at 4ᴼC for 4 weeks with minimum degradation. Meanwhile, for the detection of Mycobacterium tuberculosis from the real sample, DNA amplification step is necessary to amplify genomic MTB DNA to obtain a highly specific MTB DNA fragment sequence. Six difference samples were tested on both fabricated biosensors and demonstrate good result with real sample based on polymerase chain reaction (PCR) amplification product of M. tuberculosis DNA. Both fabricated biosensor also showed successful discrimination on the positive and negative sample with a limit of detection of 2.49 ng/μl (NH2-GO/QDs/SPCE) and 1.52 ng/μl (NH2-GO/TNCC/SPCE), respectively. Therefore, the combination of PCR amplification with electrochemical detection provides a sensitive method for specific sequence detection of mycobacterium tuberculosis (MTB).